Can globalization stop the decline in commodities' terms of trade? The Prebisch-Singer hypothesis revisited - André Varella Mollick; Jo\~ao Ricardo Faria; Pedro H. Albuquerque; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2005)
Several empirical studies report the existence of declining terms of trade between commodities and manufactures, supporting the Prebisch-Singer hypothesis. As globalization leads to greater integration of markets, we ask if in a fully integrated economy the terms of trade will display the same negative trend. Assuming that globalization would make the world economy behave as the US economy, this paper shows that the US internal real commodities' terms of trade over the 1947-1998 period experienced slowly declining but significant trends. We then test if common factors may be driving the US and international terms of trade in the long-run. The results suggest that both series, particularly those using crude materials in the numerator, share a positive long-run relationship. It follows that international integration plays no role in causing the decreasing trend of the terms of trade.
Keywords: E31; F15; F41; 330; Economic Integration; Globalisation; Prebisch-Singer